Non-immune hydrops fetalis: a case of parvovirus B19 infection in pregnancy - K., Deepthi; S., Indukala; H., Bhojaraja M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Parvovirus B19 infection during pregnancy is mostly asymptomatic, but in approximately 3% of infected women, it can cause hydrops fetalis, severe fetal anemia and even fetal demise. A 23 year old primigravida with 33+5 weeks period of gestation came to our hospital with threatened preterm labour and polyhydramnios. Ultrasound with Doppler showed features of fetal hydrops with fetal anemia. She was tested positive for parvovirus IgM and was planned for intra uterine transfusion. But patient went into preterm labour and delivered a single, stillborn, male of 2.75 kg with no visible gross anamolies. There is currently no approved vaccine or antiviral treatment for parvovirus B19 infection, but counselling of non-immune mothers and active management of confirmed maternal infections with intrauterine transfusion to correct fetal anemia is likely to improve the survival rates with significant reduction in neonatal morbidity and mortality.